Macro-financial vulnerabilities and future financial stress: assessing systemic risks and predicting systemic events - Marco Lo Duca; Tuomas A. Peltonen (European Central Bank (ECB), 2011)
This paper develops a framework for assessing systemic risks and for predicting (out-of-sample) systemic events, i.e. periods of extreme financial instability with potential real costs. We test the ability of a wide range of “stand alone” and composite indicators in predicting systemic events and evaluate them by taking into account policy makers' preferences between false alarms and missing signals. Our results highlight the importance of considering jointly various indicators in a multivariate framework. We find that taking into account jointly domestic and global macrofinancial vulnerabilities greatly improves the performance of discrete choice models in forecasting systemic events. Our framework shows a good out-of-sample performance in predicting the last financial crisis. Finally, our model would have issued an early warning signal for the United States in 2006 Q2, 5 quarters before the emergence of money markets tensions in August 2007.
Keywords: E44; E58; F01; F37; G01; 330; Asset Price Booms and Busts; Early Warning Indicators; Financial stress; Macro-Prudential Policies; Wirtschaftsindikator; Makroökonomik; Finanzkrise; Prognoseverfahren; Schwellenländer; Industrieländer